Elevated wall shear stress in aortic type B dissection may relate to retrograde aortic type A dissection: a computational fluid dynamics pilot study - Oßwald, Anja; Rengier, Fabian; Karck, Matthias; Kotelis, Drosos; Böckler, Dittmar; Ruhparwar, Arjang (European journal of vascular and endovascular surgery, 2017)
Retrograde aortic type A dissection (RTAD) is a known complication in patients with aortic type B dissection. The purpose of this computational fluid dynamics (CFD) study was to identify haemodynamic risk factors for the occurrence of RTAD.